Tropical lotic primary producers: Who has the most efficient photosynthesis in low-order stream ecosystems? - Branco, Ciro C. Z. [UNESP]; Riolfi, Thaís A. [UNESP]; Crulhas, Bruno P. [UNESP]; Tonetto, Aurélio F. [UNESP]; Bautista, Anna I. N.; Necchi Júnior, Orlando [UNESP] (Wiley, 2017)
Photosynthetic performance was assessed for the main groups of primary producers of low-order tropical streams, comprising macroalgae (11 taxa of Chlorophyta, Rhodophyta and Xanthophyta plus Cyanobacteria), bryophytes (2), angiosperms (3), and the periphytic community, by means of the Chl-a fluorescence and oxygen evolution techniques. Samples of primary producer were collected in nine stream reaches within the same drainage basin that were characterised as open or partially shaded. Low values of compensation irradiance (Ic) were found for all species tested, suggesting that they are able to maintain an autotrophic metabolism even under very low irradiances. Parameters derived from photosynthesis–irradiance curves revealed high values of the saturation parameter (Ik), associated with relative low values of photosynthetic efficiency (αETR) and photoinhibition (βETR) for species of Chlorophyta and the periphyton, suggesting adaptation to high irradiance conditions. Species of Rhodophyta, Xanthophyta, Bryophyta and angiosperms showed, in general low values of Ik and moderate to high values of αETR and βETR, indicating typical photosynthetic responses of shade-adapted plants. Chlorophyta and the periphyton showed high photosynthetic efficiency in high irradiance, and rhodophytes, bryophytes and angiosperms seemed to be more efficient in shaded stream stretches. Considering that Cyanobacteria showed high values of the photosynthesis/respiration (P/R) ratio, we suggest that this group is the most efficient primary producer in a wide range of low-order tropical streams. This physiological trait could be a feature that favours the abundance of Cyanobacteria in the benthic primary producer community, as is often reported in the literature.
Keywords: algae; Chl-a fluorescence; lotic ecosystems; macrophytes; primary production